Suppression of the TRIF‐dependent signaling pathway of TLRs by epoxomicin. Issue 9 (31st May 2021) - Kim, Su Y.; Shin, Seokwon; Kwon, Minji; Youn, Daniel; Sung, Nam J.; Kim, Na H.; Park, Sin‐Aye; Youn, Hyung‐Sun
Abstract: Toll‐like receptors (TLRs) can recognize specific signatures of invading microbial pathogens and activate a cascade of downstream signals to induce the secretion of inflammatory cytokines, chemokines, and type I interferons. The activation of TLRs triggers two downstream signaling pathways: the MyD88‐ and the TRIF‐dependent pathways. To evaluate the therapeutic potential of epoxomicin, a member of the linear peptide αʹ, βʹ‐epoxyketone first isolated from an actinomycetes strain, we examined its effects on signal transduction via TLR signaling pathways. Epoxomicin inhibited the activation of NF‐k B and IRF3 induced by TLR agonists, decreased the expression of interferon‐inducible protein‐10, and inhibited the activation of NF‐k B and IRF3 induced by overexpression of downstream signaling components of TLR signaling pathways. These results suggest that epoxomicin can regulate both the MyD88‐ and TRIF‐dependent signaling pathways of TLRs. Thus, it might have potential as a new therapeutic drug for a variety of inflammatory diseases. Abstract : The therapeutic potential of epoxomicin, a member of the linear peptide αʹ, βʹ‐epoxyketone first isolated from an actinomycetes strain, was evaluated by studying its effects on signal transduction via Toll‐like receptor (TLR) signaling pathways. The results suggest that epoxomicin can regulate both the MyD88‐ and TRIF‐dependent signaling pathways of TLRs, revealing its potential as a new therapeutic drug for various inflammatory diseases.